Effort to Prevent Anaemia during Menstruation among Female Adolescent in Islamic Boarding School - Esti Yunitasari; Praba Diyan Rachmawati; Desy Indah Nur Lestari (Universitas Airlangga, 2019)
Introduction: Female adolescents are generally prone to be infected by anaemiadue to the growing menstruation cycle which causes the loss of bloods insignificant amount every month and the needs of ferrum substance can bedoubled. The aimed of the research was to analyse factors related to the effort ofanaemia prevention during menstruation among female adolescents in Islamicboarding school.Methods: This research applied correlational descriptive design through theapproach of cross-sectional study. Total samples were 214 female students in 3Islamic boarding schools with criteria of female students aged 11-20 years oldand had experienced menstruation. Sample obtained by random sampling.Independent variables were knowledge, attitude, friends support, health facility,health efforts, and dependent variables was the efforts to prevention anaemia.Data obtained by questionnaire and analyzed by Spearman Rho with significancelevel α,0.005Results: The result showed significant correlation between knowledge (p=0.000;r=0.318). attitude (p=0.001; r=0.232). friends support (p=0.003; r=0.203). health facility (p=0.000; r=0.260). and health efforts (p=0.001; r=0.227) on prevention effort of anaemia on adolescents female menstruation in Islamic boarding school.Conclusion: Level of knowledge, posstive attitude, friends support, health facility,and health efforts can prevent anemia during menstruation.